Textbook of Preclinical Conservative Dentistry - Garg, N. Nisha; Garg, A. Amit (Jaypee Brothers Medical Publishers, 2017)
Preclinical operative dentistry is a branch of operative dentistry where practical training is given for tooth preparation and restoration of teeth with various materials on dummy models in simulated oral environment. The basic purpose of preclinical conservative dentistry is to make the students to gain expertise for restorative procedures before handling the patient. This book "Textbook of Preclinical Conservative Dentistry" consist of 14 chapters. First chapter presents an introduction to preclinical conservative dentistry. Morphology of permanent teeth and primary teeth have been discussed in second and third chapter. Structure, nomenclature and tooth physiology are covered in the fourth chapter. Chair position and dental operatory are described in the sixth chapter. Dental caries, armamentarium, principles of tooth preparation, tooth preparation for amalgam and composite restorations, and tooth preparation for primary teeth are discussed in seventh to tenth chapters. A detailed descriptions of dental materials are presented in the eleventh chapter. The twelfth chapter of this book focuses on adhesive dentistry and covers enamel bonding, dentin bonding, dentin bonding agents (DBAs) and dental composites. Basics of endodontics have been provided in thirteenth chapter. The last chapter of this book covers instruments and materials of examination spotters.